The gods in the process of Mediterranean networks: Hellenic ritesand cult practices for safe navigation in the Mediterranean - Alves Jourdan, Camila (Romanitas - Revista de Estudos Grecolatinos, 2025)
As a vital connection space, the Greeks engaged in naval practice in the Mediterranean as a fundamental component for the preservation of the polis system. However, the sea, as represented by the Greeks in textual documents, remained characterized by ambivalence, being described both as fertile – a source of fish – and as infertile – the salty sea could not sustain life like cultivated land. In order to investigate the importance of the gods and their actions in ensuring navigation safety, we will focus on debates about understanding the Mediterranean as a key element in analyses dedicated to studies of exchanges and contacts. In this context, we will examine the social condition of sailors and the performance of rituals and cult practices in their devotion to the gods, aiming to ensure a safe passage through the Mediterranean.
Keywords: Mediterranean; Navigation; Ritual; Gods